1998
DOI: 10.1111/1467-9868.00106
|View full text |Cite
|
Sign up to set email alerts
|

Weighting for Unequal Selection Probabilities in Multilevel Models

Abstract: When multilevel models are estimated from survey data derived using multistage sampling, unequal selection probabilities at any stage of sampling may induce bias in standard estimators, unless the sources of the unequal probabilities are fully controlled for in the covariates. This paper proposes alternative ways of weighting the estimation of a two-level model by using the reciprocals of the selection probabilities at each stage of sampling. Consistent estimators are obtained when both the sample number of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
383
1
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(393 citation statements)
references
References 11 publications
(10 reference statements)
2
383
1
7
Order By: Relevance
“…The estimation process was performed using the average weights per pool for simplicity, which implied that the pools should be randomly formed inside each cluster. Our results are in line with those reported by Pfeffermann et al (1998Pfeffermann et al ( , 2006 (for a normal response), by Grilli and Pratesi (2004) and Rabe-Hesketh and Skrondal (2006) (for binary outcomes in the non-grouptesting context). We found that when the sampling process is informative, weights at both levels should be included.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The estimation process was performed using the average weights per pool for simplicity, which implied that the pools should be randomly formed inside each cluster. Our results are in line with those reported by Pfeffermann et al (1998Pfeffermann et al ( , 2006 (for a normal response), by Grilli and Pratesi (2004) and Rabe-Hesketh and Skrondal (2006) (for binary outcomes in the non-grouptesting context). We found that when the sampling process is informative, weights at both levels should be included.…”
Section: Discussionsupporting
confidence: 93%
“…However, these 'raw' weights need to be scaled to be used under a mixed model approach to avoid significant bias in the parameter estimates (Pfeffermann et al, 1998). For this reason, some scaling methods have been proposed.…”
Section: Probability Of Selectionmentioning
confidence: 99%
“…MLM on survey data is an active area of research in applied statistics. The existing literature focuses on appropriate choices for weights of level-1 units when these units are selected with unequal probabilities (Pfeffermann et al 1998;Carle 2009). Level-1 weights were not an issue in this study because rooms were not randomly selected.…”
Section: Modelingmentioning
confidence: 99%
“…Simulation studies have revealed that the regression coefficients are biased for small cluster sizes [7] [8]. In the literature a cluster size greater than 20 is considered as reasonably large cluster size for 2 level data for weighted multilevel analyses [1].…”
Section: Introductionmentioning
confidence: 99%